Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.chemosphere.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of humic acids from landfill leachate on plants: An integrated approach using chemical, biochemical and cytogenetic analysis

Abstract: Biological process treatment of landfill leachate produces a significant amount of sludge, characterized by high levels of organic matter from which humic acids are known to activate several enzymes of energy metabolism, stimulating plant growth. This study aimed to characterize humic acids extracted from landfill sludge and assess the effects on plants exposed to different concentrations (0.5, 1, 2 and 4 mM C L) by chemical and biological analysis, to elucidate the influence of such organic material and minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…The presence of phenolic and other redox-active functional groups in HS accounts for their capability of reducing toxic impacts of organic and inorganic oxidizers [ 9 , 10 , 11 ], similar to the redox activity of other natural phenolic compounds [ 12 , 13 ]. The biological activity of HS is intensively discussed now [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of phenolic and other redox-active functional groups in HS accounts for their capability of reducing toxic impacts of organic and inorganic oxidizers [ 9 , 10 , 11 ], similar to the redox activity of other natural phenolic compounds [ 12 , 13 ]. The biological activity of HS is intensively discussed now [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These GI values were lower than the value obtained for HS commercial liquid fertilizer Humistar® that reached 154%. It is possible to said that HS and HA showed absence of phytotoxicity because the GI are greater than 60% [30] and confirmed that the humic susbtances have a positive effect in the plant growth [31]. Overall, it seems that leachate may be used to produce liquid organic fertilizers an important way to valuing this type of waste.…”
Section: Germination Indexmentioning
confidence: 70%
“…At the same time, there are quite numerous data in the literature on the negative effect of HS on the state of living organisms. For example, HS can also inhibit plant growth [12], cause expression of heat shock proteins [13,14], modulate biotransformation enzymes because of oxidative stress [15][16][17], inhibit photosynthetic oxygen release in plants [18][19][20][21], alter ionic homeostasis in freshwater animals [22][23][24][25], as well as have hormonelike effects on water crustaceans [26,27], amphibians [28], fish [29,30] and other animals [31,32].…”
Section: Introductionmentioning
confidence: 99%